PH sensitive chitosan-mesoporous silica nanoparticles for targeted delivery of a ruthenium complex with enhanced anticancer effects. Issue 45 (27th October 2016) - Lv, Gaochao; Qiu, Ling; Liu, Guiqing; Wang, Wei; Li, Ke; Zhao, Xueyu; Lin, Jianguo
Abstract : A pH sensitive mesoporous silica nanocarrier, RuNHC@MSNs-CTS-Biotin (CTS = chitosan), is developed for the targeted delivery and controlled release of a ruthenium(ii ) N-heterocyclic carbene (RuNHC) complex. Abstract : Nanocarriers are widely used for delivering drugs to tumors and their development is progressing steadily. In this study, a pH sensitive mesoporous silica nanocarrier, RuNHC@MSNs-CTS-Biotin (CTS = chitosan), is developed for the targeted delivery and controlled release of a ruthenium(ii ) N-heterocyclic carbene (RuNHC) complex. The RuNHC@MSNs-CTS-Biotin nanoparticles were composed of RuNHC loaded mesoporous silica nanoparticles (MSNs) coated with chitosan-biotin (CTS-Biotin) conjugates. CTS traps the RuNHC complex inside the mesopores and biotin is used as a targeting ligand to improve specific cell uptake. The particle size of RuNHC@MSNs-CTS-Biotin was around 90 nm with a zeta potential of 12.0 mV and the RuNHC loading capacity was 26.31%. The release of RuNHC from RuNHC@MSNs-CTS-Biotin was in a pH-dependent manner, and it exhibited a 59.71% terminal release ratio at pH 5.0, but almost no release under neutral conditions (pH 7.4). Its in vitro cellular uptake and anticancer activity revealed that RuNHC@MSNs-CTS-Biotin could be selectively internalized in cancer cells by biotin receptor-mediated endocytosis and this resulted in a significant improvement in anticancer activities as compared with the RuNHC complex. This multifunctional nanocarrier system provides a promising platform for the development of precisely controllable cancer therapy.